INFLUENCE OF OPERATING CONDITIONS ON THE ULTRAFILTRATION TREATMENT OF BRILLIANT BLUE BATIK DYE - Ho, Kah Chun; Selvaraj, Dinesh (Journal of Engineering & Technological Advances, 2022)
The batik industry produces a large amount of wastewater that degrades water quality. Ultrafiltration (UF) is an efficient and low-pressure filtration method for water treatment, particularly for dye wastewater. This study aims to analyze the efficiency of commercial UF polyethersulfone (PES) membranes in the treatment of brilliant blue batik dye. The effect of operating conditions involving operating pressure (2, 3, 4 bar) and pH (3, 6, and 9) of dye solution at 50 mg/L on membrane performance was evaluated via a crossflow filtration system. Higher dye rejection was obtained at close to neutral pH and higher pressure. On the other hand, the fouling propensity was mainly affected by pressure and the membrane experienced a slower flux decline at lower pressure. This is owing to the synergistic interaction between size sieving and electrostatic repulsion. The optimum membrane performance was achieved at pH 6 and 3 bar. Future studies can work on real dye wastewater produced from the batik industry.